Development of a decision support system for dam type and design, and floristic evaluation - Kaw, Kar Mun (2018)
Dams are built to provide water for domestic and industrial consumption, meet energy needs and support economic development. However, the selection of a potential dam site results in the loss of value and viability of the forests which lead to ecosystem loss and fragmentation. On the other hand, heuristic rules and empirical knowledge from experts are not readily available in the selection of the optimal type of dam and its preliminary design. Addressing these issues objectively and conveying the results effectively to the decision makers are critical in attaining sustainable development. Hence, developing a Decision Support System (DSS) prototype can help in solving these problems. This interactive computer-based system which utilized data and modules was developed using Macromedia Dreamweaver 8. It was designed based on the knowledge acquired from journals and interviews with experts within the field. There are three modules in the prototype: floristic evaluation, dam type Delphi-Analytical Hierarchy Process (D-AHP) and preliminary dam design. The floristic evaluation module aims to incorporate floristic consideration in selecting the dam site. Ecosystem loss and fragmentation were quantified by estimating the rarity of flora species and calculating the smaller and isolated ecosystem patches in each forest ecosystem respectively. The dam type DAHP module develops a set of influential attributes in selecting the optimal type of dam for the site by using Delphi technique and Analytical Hierarchy Process. The preliminary dam design module suggests the design of the type of dam at the early stage by using if-then rules. The developed DSS prototype, DSSDPro was verified using the case study of the Bengoh catchment. Based on floristic evaluation, dam site 4 is chosen to be the potential dam site as it has the least ecosystem loss (3.3km2) and fragmentation (1.5km2). By considering engineering, environmental and social factors, the type of dam that suits the chosen site is the gravity dam with the preliminary dam design of roller compacted concrete dam. DSSDPro was validated by experts who were involved in dam construction projects. The experts agree that DSSDPro is helpful in problem solving and good in its overall performance. In conclusion, the DSSDPro developed can be a significant contributor for the conservation of forest ecosystems by proposing a potential dam site based on a comprehensive attributes and rules on dam types and dam design, as well as on floristic considerations.